OPTIMASI PERENCANAAN PRODUKSI PADA PABRIK ROTI HANGAT KELILING MENGGUNAKAN METODE LINEAR PROGRAMMING - Alwi Zidan; Davanosha Ayuta Putra, Muhammad Rihan Alfiyanto, Paduloh (Jurnal Ekonomi dan Bisnis, 2025)
The Warm Bread Factory business is a major community business in economic activities in Indonesia. Especially the food industry has a very positive development and contributes greatly to national economic growth. Bread is an alternative ready-to-eat food that is quite attractive to the public because it is available in a wide selection of flavors, practical presentation, and can be enjoyed from children to the elderly. The increasing number of bread producers will have implications for the higher level of competition among bread companies. This high competition is one of the factors for the Warm Bread Business to carry out business development. This research aims to optimize production planning using Linear Programming method. This case study is applied to the production of three types of bread, namely chocolate, cheese, and mung bean bread, with the aim of maximizing profits while complying with resource constraints such as raw materials, production time, and machine capacity. Thus, the use of this method can assist the Roti Hangat Keliling Factory in planning production more effectively and efficiently.